METODE FILOSOF YUNANIMENEMUKAN TUHAN - Harahap, Aprilinda Matondang (UIN Sumatera Utara Medan, 2019)
The first hypothesis to note is that God exists, after we know the meaning of God that is so magnified by humans. Prove the existence of God is obtained by the philosophers of Ancient Greece during the preceding in the meaning and thought that is the metaphysical or empirical. Testing-testing the thinking there is that starting from the cosmological proof, psychological and moral or ethical. According to Aristotle, the cosmological proof is based on the necessity of the existence of a cause (cause effeciens) which became the origin of the change. The existence of nature and everything happens is because of the existence of God as the first Mover does not move. So did the thought of psychology that explains the presence of the Lord is evidenced by the wide range of experience of reality. The experience is really felt would show the reality, and the experience of connecting with one's deepest soul, i.e. God. The experiences of the soul will know someone that reality as a whole or keuniversalitasan is the self of God itself. The way to find God also can be proven from the side of moral (moral). This assumption predicts the existence of an inseparable relationship between the values of decency by God. The basic staples of this thinking lies in the opinion of Socrates who explained that values (morality) is the real parts was co-author of a world order. It is real value there even before the existence of mankind.